2018
DOI: 10.1021/acs.inorgchem.7b03114
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Insights into Monometallofullerene Th@C76: Strong Covalent Interaction between Thorium and the Carbon Cage

Abstract: Th@C has been studied by density functional theory combined with statistical mechanics calculations. The results reveal that Th@ T (19151)-C satisfying the isolated pentagon rule possesses the lowest energy. Nevertheless, considering the enthalpy-entropy interplay, Th@ C(17418)-C with one pair of adjacent pentagons is thermodynamically favorable at elevated temperatures, which is reported for the first time. The bonding critical points in both isomers were analyzed to disclose covalent interactions between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 55 publications
4
34
0
Order By: Relevance
“…Besides the unique electronic configuration of the metal atom in mono‐actinide EMFs, the four‐electron configuration has also led to the unexpected cage‐isomer preferences. In particular, two isomers violating the isolated pentagon rule (IPR), C 1 (17418)‐C 76 and C 1 (28324)‐C 80 , are stabilized by encapsulation of a U or a Th atom, which transfers four electrons to the cage. Commonly, non‐IPR cages containing fused pentagons are strongly destabilized as the high pyramidalization of the carbon atoms and the high local steric strain on the fused pentagons, and thus, non‐IPR cages are very limited in comparison to the common cages obeying IPR …”
Section: Monometallofullerenesmentioning
confidence: 99%
“…Besides the unique electronic configuration of the metal atom in mono‐actinide EMFs, the four‐electron configuration has also led to the unexpected cage‐isomer preferences. In particular, two isomers violating the isolated pentagon rule (IPR), C 1 (17418)‐C 76 and C 1 (28324)‐C 80 , are stabilized by encapsulation of a U or a Th atom, which transfers four electrons to the cage. Commonly, non‐IPR cages containing fused pentagons are strongly destabilized as the high pyramidalization of the carbon atoms and the high local steric strain on the fused pentagons, and thus, non‐IPR cages are very limited in comparison to the common cages obeying IPR …”
Section: Monometallofullerenesmentioning
confidence: 99%
“…Note that, although holding a formal 4+ oxidation state, the thorium cation resides close to only three pentagons of the C 3v (8)‐C 82 cage, whereas four pentagons are indispensable for thorium(IV) coordination in typical organometallic complexes such as Th( η 5 ‐C 5 H 5 ) 4 . According to the mass spectra signals of Th@C 2 n (2 n = 74‐96) reported by Chen and coworkers, the possible structures of Th@D 3h (1)‐C 74 , Th@T d (2)‐C 76 , and Th@C s (10)‐C 84 are quickly proposed by our and other's theoretical calculations . Interestingly, we found that the Th atom in Th@D 3h (1)‐C 74 may undergo an unprecedented three‐dimensional motion in the cage .…”
Section: Introductionmentioning
confidence: 98%
“…[23] According to the mass spectra signals of Th@C 2n (2n = 74-96) reported by Chen and coworkers, the possible structures of Th@D 3h (1)-C 74 , Th@T d (2)-C 76 , and Th@C s (10)-C 84 are quickly proposed by our and other's theoretical calculations. [13,[24][25][26] Interestingly, we found that the Th atom in Th@D 3h (1)-C 74 may undergo an unprecedented three-dimensional motion in the cage. [13] Besides the Th-EMFs, Echegoyen and coworkers recently obtained three uranium metallofullerenes U@D 3h (1)-C 74 , U@C 2 (5)-C 82 , and U@C 2v (9)-C 82 .…”
mentioning
confidence: 99%
“…In these structures, substantial electron densities transferred from the encapsulated metallic species to the cages are significantly localized on the fused pentagons, and stabilization results from coordination of metal ions with the pentalene units. ,, To date, various non-IPR endohedral metallofullerenes (EMFs) with metallic clusters (i.e., M 2 , M 3 N, Sc 2 S, Sc 2 O; M = group 3 elements and most lanthanides) have been isolated and structurally characterized with X-ray crystallography such as Sc 3 N@ D 3 (6140)-C 68 , Sc 2 C 2 @ C 2 v (6073)-C 68 , Sc 3 N@ C 2 v (7854)-C 70 , Sc 2 O@ C 2 (7892)­C 70 , Sc 2 S@ D 2 (10528)-C 72 , M 2 @ D 2 (10611)-C 72 (M = La, Ce), , DySc 2 N@ C s (17490)-C 76 , M 3 N@ C 2 (22010)-C 78 (M = Dy, Gd), , M 3 N@ C s (39663)-C 82 (M = Y, Gd), , and Tb 3 N@ C 5 (51365)-C 84 . In contrast, most studies of non-IPR cages stabilized by single metallic species are limited to the realm of theoretical predictions, such as Ca@C 72 , M@ C 1 (17459)-C 76 (M = Yb, Ca, Sr, Ba), , M@ C 2 v (19138)-C 76 (M = Sm, Yb, Ca, Sr, Ba), and Th@ C 1 (17418)-C 76 , whereas experimental studies are extremely rare. To the best of our knowledge, the only pristine mono-EMF possessing a non-IPR cage whose structure was unambiguously elucidated by single-crystal X-ray diffraction is Sm@ C 2 v (19138)-C 76 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent success in the synthesis and characterization of a series of actinide EMFs demonstrated that actinide EMFs show substantially different electronic and chemical properties from those of the most extensively studied lanthanide EMFs. , In particular, different from the common Ln 3+ charge state, actinides were found to adopt variable charge states depending on the cluster and the cage structures. For instance, four electrons of the Th atom are formally transferred to the C 3 v (8)-C 82 cage in Th@ C 3 v (8)-C 82 .…”
Section: Introductionmentioning
confidence: 99%